Significance of stacking fault energy in bulk nanostructured materials: Insights from Cu and its binary alloys as model systems. (April 2019) - An, X.H.; Wu, S.D.; Wang, Z.G.; Zhang, Z.F.
Abstract: Bulk nanostructured (NS) materials processed by severe plastic deformation (SPD) have received considerable attention for several decades. The physical origin of this processing philosophy is to enable substantial grain refinement from a micrometer to a nanoscale level mainly through the activation of fundamental deformation mechanisms: dislocation glide, deformation twinning, and their sophisticated interactions. The formation of nanostructures in NS metallic materials is significantly governed by the quintessential dominance of these two plasticity carriers during SPD, and their mechanical properties are thereby correspondingly affected. According to conventional crystal plasticity, the stacking fault energy (SFE) of materials is one of the most crucial factors primarily controlling which deformation mechanism plays an overwhelming role in accommodating the plasticity. Therefore, a profound understanding of the vital significance of SFE in NS materials can extend and enrich our comprehension of their structure-property relationship, lead to the design of NS metallic materials with superior properties, and pave the path for their perspective applications. Choosing Cu and its binary alloys as model systems, this review extensively surveys the principal influences of SFE on the preferred choice of deformation mechanisms during SPD, microstructural evolution, grain refinement, deformation behavior, and mechanical properties of NS material including tensile properties and cyclic deformation responses.